The magic of branding: the role of 'pledge', 'turn' and 'prestige' in fostering consumer trust in financial services - Moin, S.M.A.; Devlin, James; McKechnie, Sally (Palgrave Macmillan, 2016)
The purpose of this paper is to study the impact of brand image on consumer trust through empirical investigation in the context of financial services sector. Whilst trust helps to bind consumers to brands, a strong brand image works like magic in reducing consumers’ risk perception and promoting trust. This study analyses how brand image influences consumers’ trusting intention through operationalising an interdisciplinary brand-trust model. Constructs and measures were drawn from interdisciplinary brand and trust literature and tested through employing EFA, CFA and structural equation modelling. Data were collected through a quantitative survey of 300 financial consumers. Using the analogy of a magic trick, the study unveils the key role of financial services branding in engendering consumer trust in the ‘pledge’ or ‘prestige’ parts of the trick but not in the ‘turn’. The research contributes to the convergent and mutually inclusive theories of trust and branding as well as services marketing literature. For managers and policy makers in the financial services sector the findings will help them to effectively manage brand image and foster consumers’ trusting intention.